PENGARUH INVESTASI KOREA SELATAN MELALUI PT. HANKOOK TIRE INDONESIA TERHADAP PEREKONOMIAN MASYARAKAT JAWA BARAT - Sormin, Desri Winarti; Waluyo, Tri Joko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research discusses the effect of South Korean Investment through PT. Hankook Tire Indonesia to the economy of West Java’s people. Foreign investment becomes the object of research because as a driver of economic growth in Indonesia. Indonesia through BKBM seeks to attract foreign investors to invest in sectors to be developed under the MP3EI plan, including attracting investment from South Korea. PT. Hankook tire is one of the South Korean tire companies investing in West Java. South Korea has an industrial-based economy, one of the provinces in cooperation with South Korea in the industrial sector is West Java. The development of Java Economic Corridor has a theme of National Industry and Service Drivers. West Java plays a very important role in the economic sector at the national level. PT. Hankook tire is one of the South Korean tire companies investing in West Java.This research is a qualitative research with descriptive analysis method. In analyzing the effect of South Korean investment through PT. Hankook Tire Indonesia. The writer uses a Neoliberal perspective that supported by the concept of Multinational Cooperation (MNCs). The theory used is Foreign Direct Investment (FDI).The results of this study indicate that South Korean investment through PT. Hankook Tire Indonesia positively influences several sectors of economic development in West Java, including increased foreign investment, local economic development, increased employment and reducing local poverty, as well as the welfare of society in the corporate environment. From this result, known that South Korea's investment through PT. Hankook Tire Indonesia provides benefits to the people's economy in West Java.Keywords: FDI, West Java, PT. Hankook Tire Indonesia